Exploring responsive mathematics teaching - Lucas Revilla, Yaiza (2018)
Responsive mathematics teaching places students’ ideas and scientific thinking in a central position. It is based upon the expectation that students have resourceful scientific thinking. The responsive teacher advances the acquisition of mathematical knowledge by pursuing the substance of students’ ideas and fostering the practices of the mathematical community. This study focuses on illustrating the responsive mathematics teaching accounts of a second graders teacher.